Eskalasi Kesejahteraan Masyarakat melalui Kegiatan Penumbuhkembangan UMKM di Desa Mlopoharjo, Kabupaten Wonogiri - Sari, Rosla Tinika; Nidyah Widyamurti (Kreasi: Jurnal Inovasi dan Pengabdian kepada Masyarakat, 2024)
Mlopoharjo is a village in Wuryantoro District, Wonogiri Regency. In supporting the economy, the majority of people in Mlopoharjo work as farmers. Others work as civil servants, businessman and any other various kinds of jobs. Even though the job variants of the Mlopoharjo community are diverse, there is still a lot of village potential that has not been utilized optimally. Primarily related to the issue of household waste, agricultural and plantation by-products which are also still considered waste, as well as the development of new digital technology that is penetrating several aspects of life. Because of this, efforts were made to develop Micro, Small and Medium Enterprises (MSMEs) in Mlopoharjo Village through Village Service Activities carried out by the UNS 38 MSMEs group. For instance by processing household waste in the form of used cooking oil to become aromatherapy candles. Apart from that, the development of an entrepreneurial spirit is also carried out in children by using by-products from agriculture and plantations to be used as coloring material for ecoprint totebag. Meanwhile, to take advantage of the opportunity in the digitalization era to develop community businesses, it was also done by providing outreach regarding digital technology which can be useful for turning the wheels of the community's economy. Socialization is carried out by inviting MSMEs' players to practice producing product photos that are useful for branding as well as providing information related to digital payments that integrate various types of QR from various payment system service providers in QRIS. The aim is of course none other than so that the community can optimize village potention in realizing welfare. The result is that the community continues efforts for village development even though the Village Service Activity for the July-August 2023 period has ended.